CYP2C19 and PON1 polymorphisms regulating clopidogrel bioactivation in Chinese, Malay and Indian subjects. (April 2012) - Chan, Mark Y; Tan, Karen; Tan, Huay-Cheem; Huan, Pei-Tee; Li, Bei; Phua, Qian-Hui; Lee, Hong-Kai; Lee, Chi-Hang; Low, Adrian; Becker, Richard C; Ong, Wen-Chong; Richards, Mark A; et al.
Aim, materials & methods: We investigated the functional significance of CYP2C19*2, *3, *17 and PON1 Q192R SNPs in 89 consecutive Asian patients on clopidogrel treatment and the prevalence of functionally significant polymorphisms among 300 Chinese, Malays and Asian Indians.Results: Both CYP2C19 loss-of-function alleles ( *2 or *3 ) were associated with higher platelet reactivity while the CYP2C19 gain-of-function allele ( *17 ) had lower platelet reactivity. For PON1, the median PRI was not significantly different between the QQ, QR and RR groups. The allele frequencies of CYP2C19*2, CYP2C19*3 and CYP2C19*17 were 0.280, 0.065 and 0.010 (rare) for Chinese, 0.310, 0.050 and 0.025 for Malays, and 0.375, 0.010 (rare) and 0.165 for Indians, respectively.Conclusion: Our data suggest that genotyping studies to investigate clopidogrel response should include CYP2C19*2 and *3 but not *17 polymorphisms in Chinese, and CYP2C19*2 and *17 polymorphisms but not *3 in Indians. All three polymorphisms should preferably be genotyped in Malays. Original submitted 16 December 2011; Revision submitted 16 February 2012